Effects of Bank Capital on Profitability and Credit Risk: The Case of Vietnam's Commercial Banks - Nguyen, Thi Hong Vinh (University of Economics Ho Chi Minh City, 2023)
This paper seeks to examine the effects of bank capital on profitability and credit risk of 30 Vietnam’s commercial banks from 2007 to 2014. Using the system generalized method of moments (GMM), the paper conducts several tests on the moral hazard and regulatory hypotheses on the relationships among bank capital, profitability, and credit risk. With no regard to other determinants, its results indicate that the effects are evident, i.e. bank risk is found to impact differently on bank returns, and it is also negatively associated with credit risk of commercial banks in Vietnam.